Available evidence points to low effectiveness of influenza vaccines for older people. Issue 4 (22nd June 2010) - Simonsen, Lone
Abstract : Commentary on: Jefferson T Di Pietrantonj C Al-Ansary LA . Vaccines for preventing influenza in the elderly. Cochrane Database Syst Rev 2010 ;2 :CD004876 .